If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 66 + -6x = 21x + 24 Reorder the terms: 66 + -6x = 24 + 21x Solving 66 + -6x = 24 + 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. 66 + -6x + -21x = 24 + 21x + -21x Combine like terms: -6x + -21x = -27x 66 + -27x = 24 + 21x + -21x Combine like terms: 21x + -21x = 0 66 + -27x = 24 + 0 66 + -27x = 24 Add '-66' to each side of the equation. 66 + -66 + -27x = 24 + -66 Combine like terms: 66 + -66 = 0 0 + -27x = 24 + -66 -27x = 24 + -66 Combine like terms: 24 + -66 = -42 -27x = -42 Divide each side by '-27'. x = 1.555555556 Simplifying x = 1.555555556
| TC=10+5Q | | 3.92/0.8 | | 12x-4y=0 | | 3x=45+2x | | 2a(3d+2)= | | 6.0x-20=20 | | 72(8/12x)-106(-17-8) | | 53+2x=x+111 | | 10y+y^10=1100 | | (4x-5)(2x+9)=0 | | 3x+8=64-6x | | 12(28-3x)+90(-30+3)= | | 426*15= | | -4x-2a= | | (.75)x+(.625)-(.5)x=(1.5)x-(2.5) | | (5x+2)/(4x+7)=x | | (5x+2)/(4x+7) | | (3/4)x-6=x+5 | | 1-1/x-8 | | 1+1/x-8 | | -8x+10=5x+9 | | 2(x-5)(x-5)=0 | | xx-2x+1=0 | | (3d-7)+8=0 | | 7/4u=1/2-1/6v | | y+-4y=118 | | 5x-(17*13)/122=2 | | (6y+5)+(2y-6)=118 | | (6y+5)+(2y-6)= | | 1x+20+2x=-10-2x-15 | | 16x+8x=192 | | 9+3x=14+2x |